Drinking for protection? Epidemiological and experimental evidence on the beneficial effects of coffee or major coffee compounds against gastrointestinal and liver carcinogenesis - Romualdo, Guilherme Ribeiro [UNESP]; Rocha, Ariane Bartolomeu [UNESP]; Vinken, Mathieu; Cogliati, Bruno; Moreno, Fernando Salvador; Chaves, María Angel García; Barbisan, Luis Fernando [UNESP] (Elsevier, 2019)
Recent meta-analyses indicate that coffee consumption reduces the risk for digestive tract (oral, esophageal, gastric and colorectal)and, especially, liver cancer. Coffee bean-derived beverages, as the widely-consumed espresso and “common” filtered brews, present remarkable historical, cultural and economic importance globally. These drinks have rich and variable chemical composition, depending on factors that vary from “seeding to serving”. The alkaloids caffeine and trigonelline, as well as the polyphenol chlorogenic acid, are some of the most important bioactive organic compounds of these beverages, displaying high levels in both espresso and common brews and/or increased bioavailability after consumption. Thus, we performed a comprehensive literature overview of current knowledge on the effects of coffee beverages and their highly bioavailable compounds, describing: 1)recent epidemiological and experimental findings highlighting the beneficial effects against gastrointestinal/liver carcinogenesis, and 2)the main molecular mechanisms in these in vitro and in vivo bioassays. Findings predominantly address the protective effects of coffee beverages and their most common/bioavailable compounds individually on gastrointestinal and liver cancer development. Caffeine, trigonelline and chlorogenic acid modulate common molecular targets directly implicated in key cancer hallmarks, what could stimulate novel translational or population-based mechanistic investigations.
Keywords: Caffeine; Chlorogenic acid; Espresso and common coffee; Gastrointestinal cancer; Liver cancer; Trigonelline